2017
DOI: 10.35172/rvz.2017.v24.288
|View full text |Cite
|
Sign up to set email alerts
|

Utilização da ultrassonografia transabdominal para auxilio propedêutico em equinos com síndrome cólica

Abstract: O abdome agudo na espécie equina é considerado uma emergência, sendo de grandeimportância a determinação precoce da necessidade ou não da intervenção cirúrgica comomedida terapêutica. Os objetivos dessa descrição de casos foram: identificar quais os achadosultrassonográficos (US) que auxiliam na determinação do paciente clínico ou cirúrgico, qual apossibilidade de identificação da causa da cólica e expor as dificuldades de execução datécnica. Foi realizado um estudo prospectivo observacional para análise ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
2
4
0
1
Order By: Relevance
“…This is because when observing the same loop, it does not always stretch in the same way and to the same extent. The mean of the largest diameter of the jejunal loops, in cross-section, was 44.8±7.3 mm, with a wall thickness of 2.5±0.3 mm in another abdominal imaging study (Amaral and Froes, 2014), being similar to the measurements found in adult animals in this study. Peristaltic waves, anechoic fluid, and hyperechoic gas are often seen in its lumen (Reef, 2003).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This is because when observing the same loop, it does not always stretch in the same way and to the same extent. The mean of the largest diameter of the jejunal loops, in cross-section, was 44.8±7.3 mm, with a wall thickness of 2.5±0.3 mm in another abdominal imaging study (Amaral and Froes, 2014), being similar to the measurements found in adult animals in this study. Peristaltic waves, anechoic fluid, and hyperechoic gas are often seen in its lumen (Reef, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…Zootec., v.75, n.2, p.191-198, 20232015. A good agreement has already been observed between the measurements of intestinal layers in histological and ultrasound examinations for the duodenum, jejunum, cecum, small colon, and right dorsal large colon (Bevevino et al, 2021).…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…O diagnóstico de enterolitíase, em alguns casos pode ser realizado através de palpação retal, identificando-o como uma massa compactada (NAKAMAE et al, 2018). O exame de ultrassonografia transabdominal, somado as outras análises necessárias têm auxiliado de forma eficiente na determinação da escolha por uma conduta clínica ou cirúrgica em equinos com síndrome cólica (AMARAL et al, 2017). Além disso, a radiografia abdominal pode demonstrar o enterólito e a tomografia computadorizada é capaz de identificar o número de enterólitos, localização exata e tamanho dos mesmos (NAKAMAE et al, 2018).…”
Section: Enterolitíase Em Equinosunclassified